A Longitudinal Study of Plasma pTau181 in Mild Cognitive Impairment with Lewy Bodies and Alzheimer's Disease. Issue 7 (23rd March 2022) - Thomas, Alan J.; Hamilton, Calum A.; Heslegrave, Amanda; Barker, Sally; Durcan, Rory; Lawley, Sarah; Barnett, Nicola; Lett, Debbie; Firbank, Michael; Roberts, Gemma; Taylor, John‐Paul; Donaghy, Paul C.; et al.
Abstract: Background: Alzheimer's disease (AD) co‐pathology is common in dementia with Lewy bodies and is associated with increased decline. Plasma pTau181 is a blood‐based biomarker that can detect AD co‐pathology. Objectives: We investigated whether pTau181 was associated with cognitive decline in mild cognitive impairment with Lewy bodies (MCI‐LB) and MCI with AD (MCI‐AD). Methods: We assessed plasma pTau181 using a single‐molecule array (Simoa) immunoassay at baseline and follow‐up in a longitudinal cohort of MCI‐LB, MCI‐AD, and controls. Results: One hundred forty‐six subjects (56 probable MCI‐LB, 22 possible MCI‐LB, 44 MCI‐AD, and 24 controls) were reviewed for up to 5.7 years. Probable MCI‐LB had significantly higher pTau181 (22.2% mean increase) compared with controls and significantly lower (24.4% mean decrease) levels compared with MCI‐AD. Receiver operating characteristic analyses of pTau181 in discriminating probable MCI‐LB from controls showed an area under the curve (AUC) of 0.68 (83% specificity, 57% sensitivity); for discriminating MCI‐AD from healthy controls, AUC was 0.8 (83.3% specificity, 72.7% sensitivity). pTau181 concentration was less useful in discriminating between probable MCI‐LB and MCI‐AD: AUC of 0.64 (71.4% specificity, 52.3% sensitivity). There was an association between pTau181 and cognitive decline in MCI‐AD but not in MCI‐LB. In a subset with repeat samples there was a nonsignificant 3% increase per follow‐up year in plasma pTau181. The rate of change in pTau181 was not significantly different in different diagnostic subgroups. Conclusions: pTau181 was not associated with an increased decline assessed using either baseline or repeat pTau181. pTau181 partially discriminated probable MCI‐LB from controls and MCI‐AD from controls but was not useful in distinguishing probable MCI‐LB from MCI‐AD. © 2022 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society Abstract : Elevated plasma pTau181 is specifically associated with a declining cognitive trajectory in mild cognitive impairment due to Alzheimer's disease. However, this is not the case in probable mild cognitive impairment with Lewy bodies: whereas many who decline have elevated pTau181 concentrations, many also decline who do not.